Smartphone Uses in the Language Classroom for Learning Purposes by EFL College Students - Mahmoud Ahmad Thabet Al-maqtri (Taez University, 2020)
This study aimed at examining the current uses of smartphones for language learning purposes by the EFL college students outside the classroom with the intention of proposing using these devices for language learning inside the classroom. The study was conducted with students of English in two colleges of Sciences and Arts affiliated to the University of Bisha, An-namas, Saudi Arabia, in 2018-2019. In this mixed-methods descriptive study, a questionnaire was used to collect the data from 77 male and female participants taken from a total population of 142 students. The Questionnaire validity (ɑ= 0.87) and reliability were measured. To analyze the obtained data, the (SPSS) version16.0 was used. Qualitative data from the researcher-instructor's informal observations and colleagues' discussions were used to support data gained from the questionnaire. Results showed that participants have already been using these devices for learning purposes outside the classroom. According to the findings, the five top uses of smartphones by the respondents were (1) in using these devices as dictionaries; (2) for logging in the electronic portal to follow up notices and so on; (3) in spelling check (4) in translating texts, and (5) in looking for answers to difficult questions. Other uses were also given. T-test did not show any significant gender differences in the uses of these devices. Statistics indicated that all participants wanted to use these devices in classroom. The study concluded that these devices could be used in the classroom for language learning purposes. A list of uses and applications was prepared for the purpose. Among the recommendations was to establish a clear policy and rules to be followed by the different parties.